2003
DOI: 10.1002/gcc.10242
|View full text |Cite
|
Sign up to set email alerts
|

Synovial fibroblasts and synovial macrophages from patients with rheumatoid arthritis and other inflammatory joint diseases show chromosomal aberrations

Abstract: Chromosomal aberrations were comparatively assessed in nuclei extracted from synovial tissue, primary-culture (P-0) synovial cells, and early-passage synovial fibroblasts (SFB; 98% enrichment; P-1, P-4 [passage 1, passage 4]) from patients with rheumatoid arthritis (RA; n = 21), osteoarthritis (OA; n = 24), and other rheumatic diseases. Peripheral blood lymphocytes (PBL) and skin fibroblasts (FB) (P-1, P-4) from the same patients, as well as SFB from normal joints and patients with joint trauma (JT) (n = 4), w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 36 publications
0
11
0
Order By: Relevance
“…We thus suggested that trisomy 5 should be considered as a non-random in vitro event of unknown significance at present. On the other hand trisomy 7 has not been previously described in hematologic malignancies, but is a common finding in malignant and non-malignant tissues [147][148][149]. The frequency of trisomy 7 seems to increase with age and its presence might be associated with aging rather than with the disease per se [148].…”
Section: Qualititative and Quantitative Characteristics Of Bm-mscs Inmentioning
confidence: 88%
“…We thus suggested that trisomy 5 should be considered as a non-random in vitro event of unknown significance at present. On the other hand trisomy 7 has not been previously described in hematologic malignancies, but is a common finding in malignant and non-malignant tissues [147][148][149]. The frequency of trisomy 7 seems to increase with age and its presence might be associated with aging rather than with the disease per se [148].…”
Section: Qualititative and Quantitative Characteristics Of Bm-mscs Inmentioning
confidence: 88%
“…Regarding internal molecular changes in the individuals, a participation of mutations or single nucleotide polymorphisms in different genes is plausible, either directly [ 45 , 46 ] or via mutated regulators (for example, transcription factors, mRNA stability modifiers, and so on [ 47 ]). This also includes broader genomic rearrangements (for example, chromosomal translocations or polysomies [ 48 , 49 ]) as well as epigenomic modifications (for example, gene/promoter methylation [ 50 ]). In addition, the individual composition of cell types in the analyzed SM samples may influence the mRNA expression profile, depending on the inflammatory status and/or cell proliferation, potentially resulting in enhanced immigration/proliferation of T cells, B cells, or synovial fibroblasts [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…After the introduction of molecular cytogenetics [4-7], it became even possible to analyze numerical chromosomal aberrations in non-dividing cells [8]. By that also low-level chromosomal aberrations could be detected in tumor [9-13], various clinical [14-18] and neuronal diseases [19-27], embryonic tissues [28-32] and different tissue types [9, 13, 15, 33-35]. Overall it can be stated that chromosome instability is one of the main causes of large-scale genome variation [36-39].…”
Section: Small Supernumerary Marker Chromosomes (Ssmc)mentioning
confidence: 99%